The COVID-19 pandemic: resilient organisational response to a low-chance, high-impact event. Issue 3 (18th May 2020) - Lloyd-Smith, McKenzie
Abstract : The global healthcare sector is currently in the midst of the COVID-19 pandemic, a 'low-chance, high-impact' event which will require healthcare systems, and the organisations within them, to maintain organisational resilience in order to respond effectively. However, contrary to the instinctive reaction to tighten control, the quality of response depends on healthcare systems' capacity to loosen control and, subsequently, enhance improvisation. Three factors critical to enhancing an organisation's capacity for improvisation are highlighted; increasing autonomy, maintaining structure and creating a shared understanding. By drawing on the case of Christchurch Hospital's response to a major earthquake, this paper demonstrates the vital role that improvisation can play within a clinical setting, when responding to a low-chance, high-impact event.